Tata Ruang Hunian Pengrajin Akar Jati Desa Tempellemahbang Kabupaten Blora - WENTI HIDAYAH NUR SYADZA; Jenny Ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Tempellemahbang village is one of the villages which produce teak root craft in Blora town. In 2008 Tempellemahbang community realized that the teak root as one of material that has high artistic value if processed properly, with the increasing demand of teak root craft, many people were interested to become teak root craftsmen. In the residential of teak root craftsman there is a change of occupancy dwelling either macro, meso and micro that is associated with the typology of residential space. The purpose of this study is to determine the layout of the home teak root craftsmen in accordance with the activities of craftsmen and related factors to be the basis of the concept of settlement arrangement of craftsmen. The research method used is descriptive- qualitative with field data collection is done by observation method and observation of observated object. The results obtained by the analysis of spatial layout based on community activities related elements of nature, network, society, man and shells are divided into macro, meso and micro of residential spatial . The macro pattern of settlements formed based on the natural structure commonly called the organic pattern. Macro spatial residential contained in this research is the discovery of irregular path patterns on the settlement. In the micro occupancy is divided into two typologies there is typology of mixed space (production room is in the one building with residence) and the typology of separate spaces (production room is in the different buildings with residence).